Remarkable Variation in Phytochemicals of Ferula gummosa Bioss. Essential Oils Collected From Different Parts of Iran - Saied Goodarzi*; Mansour Mofasseri; Zahra Tofighi; Mostafa Pirali Hamedani; Abbas Hadjiakhoondi; Saeed Tavakoli; Zahra Moein; Zahra Baharipour (Iranian Society of Pharmacognosy, 2022)
Background and objectives: The oleo-gum resin from Ferula gummosa Bioss. is commercially important. Variability of geographic location has shown a deep effect on essential oil of different genus of plants. Thus, evaluation of oleo-gum resin of Ferula gummosa from different locations is important for further studies. In the present study, phytochemicals profile of essential oil of oleo-gum resins from F. gummosa in different geographic location and various bioclimates of Iran, were studied. Methods: The oleo-gum resin of F. gummosa was collected from different regions of Iran. The essential oils of the samples were extracted by Clevenger apparatus and were analyzed by GC-MS. Results: The highest amount of essential oil compared was observed in the samples from Damghan area (24.0%), Firuzkuh area (22%) and Kalat-e-Naderi area (22%). The variability in the oil composition of different samples exhibited a notable difference in monoterpenes content from 39.15 % to 87.48%. Based on GC-MS analysis, the major components were β-pinene (5.11-63.80 %), sabinene (3.37-30.69%), α-pinene (4.43-12.72%) and δ-carene (2.38-10.23 %). The highest concentrations of β-pinene (63.80%) and sabinene (30.69%) were observed in the Shiraz and Torbat-e-Jam essential oils, respectively.  The highest amounts of α-pinene (12.72%) and δ-carene (10.23%) were recorded in Firuzkuh and Shiraz areas, respectively. Conclusion: Significant variation in the component of the essential oils from different oleo-gum resins can be used to improve the knowledge about the endemic medicinal plants.